Adaptive changes of coral Galaxea fascicularis holobiont in response to nearshore stress - Zhu, Wentao; Zhu, Ming; Liu, Xiangbo; Xia, Jingquan; Wang, Hao; Chen, Rouwen; Li, Xiubao (Frontiers in Microbiology, 2022)
Global change and local stressors are simultaneously affecting the nearshore corals, and microbiome flexibility may assist corals in thriving under such multiple stressors. Here, we investigated the effects of various environmental variables on Galaxea fascicularis holobiont from nearshore and offshore reefs. These nearshore reefs were more turbid, eutrophic, and warm than offshore reefs. However, coral physiological parameters did not differ significantly. Corals under stressful nearshore environments had low symbiont diversity and selected more tolerant Symbiodiniaceae. The bacterial diversity of offshore corals was significantly higher, and their community composition varied obviously. Diffusion limitations and environmental heterogeneity were essential in structuring microbial communities. Functional annotation analysis demonstrated significant differences between nearshore and offshore corals in bacterial functional groups. Environmental stress significantly reduced the complexity and connectivity of bacterial networks, and the abundances of keystone taxa altered considerably. These results indicated that corals could thrive nearshore through holobiont plasticity to cope with multiple environmental stresses.